Uses of Published Research: An Exploratory Case Study - Fahy, Patrick J. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
Academic publications are too often ignored by other researchers. There are various reasons: Researchers know that conclusions may eventually be proved wrong; publications are sometimes retracted; effects may decline when studied later; researchers occasionally don’t seem to know about papers they have allegedly authored; there are even accusations of fraud (Cohen, 2011). In this exploratory case study, 10 papers were examined to determine the various ways they were used by others, whether there were cases of reported effects declining, and whether, among those who referenced the papers, there were suggestions that anything in the papers ought to be retracted. Findings showed that all the papers had been referenced by others (337 user publications were found, containing a total of 868 references). Other findings include the following: Single references were far more common than multiple references; applications/replications were the least common type of usage (23 occurrences), followed by contrasts/elaborations (34), and quotations (65); unlike reports regarding publications in the sciences, whether the paper was solo- or co-authored did not affect usage; appearance in a non-prestige journal was actually associated with more usage of some kinds; and well over 80% of uses were in heavily scrutinized sources (journal articles or theses/dissertations). The paper concludes with recommendations to writers about how to avoid producing publications that are ignored.